ANALISIS KELAYAKAN USAHA MANISAN BELIMBING DI UMKM KELURAHAN KARANGSARI KECAMATAN SUKOREJO KOTA BLITAR - Lestari, Silvi; Wahyu Budiman, Eko (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2023)
This research aims to know the process of production of candied starfruit business in UMKM Karangsari Village, know the analysis of financial feasibility of candied star fruit in UKM Karangsari Village, know the sensitivity analysis of business candied starfruit in UMKM Karangsari Village. The research method used in this study is a quantitative descriptive method, which is interpreted as research that presents data by analyzing the data obtained so as to get a clear picture. Quantitative descriptive method is a method that emphasizes the objective measurement aspects of social phenomena, quantitative research is processed and analyzed with statistics. The results showed that the production process was carried out in the candied star fruit business in Karangsari Sub-District when viewed from the nature of the production process, namely the type of synthetic production due to physical or chemical changes, namely the change in star fruit into candied star fruit. Based on the financial analysis that has been carried out, the Karangsari Agro-farming business is feasible to run. This can be seen from (1) The results of the NPV (Net Present Value) analysis yield a value greater than 0, namely 92,053,747.80 (2) The results of the analysis of Net Benefit Cost ratio (Net B/C) obtained results of 1.23 (3) The results of Internal Rate analysis of Return (IRR) is 95%, (4) Payback Period analysis results are 2.3 (5) Sensitivity analysis results for net benefits and operational maintenance show that this business is still safe if there are changes in the factors that influence it.